Clinical study on endovascular recanalization of non-acute symptomatic middle cerebral artery occlusion - Xia, Jinchao; Li, Hao; Zhang, Kun; Wang, Ziliang; Li, Tianxiao (Frontiers in Neurology, 2023)
Objective Endovascular recanalization in patients with non-acute symptomatic middle cerebral artery occlusion remains clinically challenging. Here, we aimed to evaluate the feasibility and safety of endovascular recanalization for non-acute symptomatic middle cerebral artery occlusion and propose a new patient classification. Methods Between January 2019 and December 2021, 88 patients with non-acute symptomatic middle cerebral artery occlusion underwent prospective endovascular recanalization at our hospital. All patients were divided into three groups according to occlusion length, occlusion duration, occlusion nature, calcification of the occlusion site, and occlusion angulation. The indicators of each group were analyzed, including general baseline data, imaging data, surgical conditions, and follow-up results. Results Of the 88 patients, 73 were successfully recanalized and 15 were abandoned because the instruments either could not reach the distal true lumen of the occlusion or broke through the blood vessels. The overall technical success rate was 83.0% (73/88), and perioperative complications occurred in 15 patients. Preoperatively, all patients were divided into three risk groups: low, medium, and high. From the low- to high-risk groups, the recanalization rate gradually decreased (100.0, 91.7, and 16.7%, respectively, P = 0.020), the perioperative complication rate gradually increased (0, 13.9, and 83.3%, respectively, P < 0.001), the proportion of the modified Rankin scale scores >2 at 90 days increased (0, 11.7, and 50.0%, P < 0.001), and the restenosis/reocclusion rates in the 73 cases of successful recanalization increased (0, 16.1, and 100%, P = 0.012) during follow-up. Conclusion Endovascular recanalization may be feasible and safe in well-selected patients with non-acute symptomatic middle cerebral artery occlusion, especially in the low- and medium-risk groups.